Distribution patterns of the Baraba buzzing grasshopper Angaracris barabensis (Pallas) (Orthoptera: Acrididae) - A. I. Pashkova; V. V. Molodtsov; S. Yu. Storozhenko; N. S. Baturina; K. V. Popova; O. V. Yefremova; M. G. Sergeev (Юг России: экология, развитие, 2025)
Aim. Angaracris barabensis is widely distributed across the Asian grasslands. It is often qualified as one of the important pests. The aim of the paper is to estimate possible shifts of its distribution relative to global warming. The geographic coordinates of 384 localities were determined for the species. Two different approaches to species distribution modelling (maximum entropy and multidimensional ellipsoid envelope) were used. The general patterns of distribution were described. Several models of the species distribution were generated and compared. The main factors of its distribution are revealed. Ecological modelling predicts opportunity of possible northward shifts of the species range in Central and East Siberia and persistence of areas of possible harmfulness in South Siberia, Mongolia and North China. Our predictions show two opposite trends. In the western and southeastern parts of the species range, suitability of conditions will decrease. In the central and north‐eastern parts, the suitability will remain almost the same or even increase. The comparative analysis shows there are no evident contemporary shifts of range boundaries of A. barabensis associated with global warming per se or this tendency is extremely weak. However, the distribution of suitable conditions can change significantly during the next several decades.